2004
DOI: 10.1108/09564230410540953
|View full text |Cite
|
Sign up to set email alerts
|

Online service quality dimensions and their relationships with satisfaction

Abstract: Emerald Article: Online service quality dimensions and their relationships with satisfaction: A content analysis of customer reviews of securities brokerage services Zhilin Yang, Xiang Fang Article information:To cite this document: Zhilin Yang, Xiang Fang, (2004),"Online service quality dimensions and their relationships with satisfaction: A content analysis of customer reviews of securities brokerage services"Access to this document was granted through an Emerald subscription provided by NORTH CAROLINA STATE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
96
0
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 377 publications
(147 citation statements)
references
References 47 publications
9
96
0
6
Order By: Relevance
“…Reliability can be formed of right order completion, precise records; precise quote, accurate bills, precise outcomes and credibility in the services. Yang and Fang (2004) indicated that reliability is the most important factor in banking services. A study done by Parasuraman et al (1985) stated that service quality was performed in four different companies, those companies include banks, maintenance service, companies credit card, and companies and telecommunication companies.…”
Section: Service Quality Dimensionsmentioning
confidence: 99%
“…Reliability can be formed of right order completion, precise records; precise quote, accurate bills, precise outcomes and credibility in the services. Yang and Fang (2004) indicated that reliability is the most important factor in banking services. A study done by Parasuraman et al (1985) stated that service quality was performed in four different companies, those companies include banks, maintenance service, companies credit card, and companies and telecommunication companies.…”
Section: Service Quality Dimensionsmentioning
confidence: 99%
“…Moreover, the way in which electronic service quality (e-SQ) positively influences online businesses success has been established in the literature (Yang & Fang, 2004;Zeithaml, Parasuraman, & Malhotra, 2002). This relationship often leads to customer purchase intentions (Aladwani, 2006), customer satisfaction (Kim & Stoel, 2004), website brand equity (Tsao & Tseng, 2011) and online loyalty (Flavián, Guinalíu, & Gurrea, 2006;Gounaris, Dimitriadis, & Stathakopoulos, 2010;Marimon, Petnji, & Casadesus, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to previous studies, the dimensions and their related items developed in this research comprise a relatively comprehensive pool of measures for assessing online services and can serve as building blocks for further studies in relationship marketing (Yang & Fang, 2004). We further reveal that major drivers of online service satisfaction are still strongly tied to traditional service quality gap factors and can be customized to the context of Internet-related contents.…”
Section: Resultsmentioning
confidence: 95%